A long-term survival case after resection of the pancreatic metastasis from lung cancer. (2019) - Kageyama, Yumiko; Yamaguchi, Ryuzo; Watanabe, Shinya; Aizu, Keiji; Sato, Fumiya; Fujieda, Hironori; Yamada, Mihoko; Toyoda, Yoshitaka; Iwata, Tsutomu
Highlights: Significance of resection in patients with pancreatic metastasis from lung cancer. A long-term survivor of pancreatic metastasis from lung cancer after pancreatectomy. Consider resection if the disease is localized and the patient's condition is good. Abstract: Introduction: Pancreatic metastasis from lung cancer is not an indication for surgical resection because patients with such a condition present with multiple-organ metastases. Therefore, the significance of resection in patients with pancreatic metastasis from lung cancer remains unclear. Here we report a case of a long-term survivor of pancreatic metastasis from lung cancer after pancreatectomy. Case presentation: A 67-year-old woman presented with a pancreatic mass. She had undergone left lower lobectomy for stage IIIA lung adenocarcinoma 6 years prior to presentation. Following surgery, she received adjuvant treatment with gefitinib for 7 months. However, this treatment was discontinued due to its side effects. The patient received radiation therapy for mediastinal lymph node metastasis 2 years after resection and she became cancer-free. Six years after the initial pulmonary resection, the patient's tumor marker level increased, and abdominal computed tomography (CT) revealed a 20-mm tumor in the pancreatic tail. Positron emission tomography–CT revealed an abnormal uptake in the pancreatic tail. However, no other abnormal lesions were observed. The diagnosis was primary pancreatic cancer or metastasis from lung cancer. Distal pancreatectomy with lymph node dissection was performed, and the pathological diagnosis was metastasis from lung cancer. The patient survived for more than 5 years without recurrence but she died of acute renal failure after acquiring pneumonia. Conclusion: Surgical treatment should be considered for pancreatic metastasis from lung cancer if the disease is localized and the patient's condition is good. Additionally, combined therapy, including surgical resection, may be effective for repeated recurrence.